THE CONTRIBUTION OF ISLAMIC RELIGIOUS EDUCATION (PAI) MATERIALS TO THE DEVELOPMENT OF STUDENTS’ TOLERANT AND INTEGRATIVE ATTITUDES - Hasniah Hasniah; Misbahul Fuad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This research aims to analyze the contribution of Islamic Education materials in developing students' tolerant and integrative attitudes. The research method employs a qualitative approach with library research that analyzes relevant literature from the 2021-2025 period. The research findings indicate that Islamic Education materials have comprehensive dimensions in forming students' tolerant character through the concept of tasamuh and universal Islamic values. The implementation of religious moderation in Islamic Education learning proves effective in developing balanced and inclusive religious attitudes. The development of integrative attitudes occurs systematically through the internalization of contextual Islamic values. Factors influencing the success of implementation include teacher competence, institutional support, student characteristics, and socio-cultural context. This research recommends curriculum reform, teacher competence enhancement, and strengthening the synergy of educational tri-centers to optimize the contribution of Islamic Education materials in forming students' tolerant and integrative character sustainably.